Preventive effect of Bacillus mojavensis levan against carbon tetrachloride and cisplatin toxicity: in vivo study - Haddar, Anissa; Feriani, Anouar; Hamed, Mariem; Sila, Assaad; Ellouz-Chaabouni, Semia (Environmental science and pollution research international, 2021)
This study is the first to investigate the hepato- and nephron-preventive effect of levan from Bacillus mojavensis (BM-levan) against toxicity induced by carbon tetrachloride (CCl 4 ) and cisplatin. Thirty-six male albino rats weighing between 230 and 250 g were used for this experiment. The groups received multiples doses of BM-levan and were compared to the untreated group. The in vitro and in vivo biological potentials of BM-levan were evaluated by measuring its antioxidant capacity as well as its hepato- and nephron-protective activities in rat models. The investigations highlighted a significant in vitro antioxidant activity indicated by the radical-scavenging capacity, the reducing power, and the total antioxidant activity measurement. In addition, results demonstrate that BM-levan supplementation during 8 weeks (100 mg/kg body weight) significantly ( p < 0.05 ) decreased aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities and remarkably ( p < 0.05 ) attenuated the altered lipid profile by decreasing the levels of triglycerides (TG) and total cholesterol (TC), LDL cholesterol (LDL-C) and by enhancing the HDL cholesterol (HDL-C) content, when compared with the CCl 4 group. BM-levan also reduced the content of plasma renal biomarkers (urea, creatinine, and uric acid) in the cisplatin-treated group. Moreover, BM-levan inhibited hepatic and renal oxidative stress generated by CCl 4 and cisplatin administration, through the enhancement of the antioxidant catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) and the diminishment of lipid peroxidation. The harmful effects of CCl 4 or cisplatin on hepatic and renal histology were found to be decreased by the addition of BM-levan. Therefore, BM-levan has proved promising for biomedical applications thanks to its in vitro and in vivo antioxidant properties.